Family business in tourism characteristics : the owner's perspective - Bujan, Ivana (Array, 2020)
Tourism and family entrepreneurship make a significant contribution to the Croatian economy, therefore it is important to define characteristics and business operations of family business in tourism. This paper examines characteristics of small family businesses in tourism from the perspective of owners of small family hotels in Croatia. In this qualitative study, interview was employed as a primary research instrument and the scientific method used is based on gestalt principles. GABEK©, a specific method of qualitative research and text analysis was used. The paper portrays the aspects of chosen business characteristics of small families in tourism - motivation of owners when setting up a business, success of small family business, financing, business issues, business facilitation and innovativeness. For each business aspect gestalten tree was formed with owner`s aggregated statements and finally the gestalten tree containing all chosen business aspects has been formed. Motives are, as presumed, family oriented and tending to preserve the family vision in the future. Qualitative, non-financial success measures are more important than financial measures. Business is usually financed from own funds and by combining bank loans, while business issues imply too high tax rates. Innovativeness levels are low which relates to low education levels. Originality of the research can be found in the fact that no similar study was conducted for Croatia nor as GABEK© method was used for qualitative data analysis. The research contributes to the scarce scientific research corpus in the field of family business in tourism. Practical implications presuppose education suggestions for family members in family firms - business facilitation suggestions and detected business issues.